ANIMISME DAN DINAMISME DALAM DRAMA ROH KARYA WISRAN HADI SERTA KORELASINYA DENGAN BUDAYA DI SUMATERA BARAT: SEBUAH BENTUK PERWUJUDAN UNSUR EKSTRISNIK DRAMA - Nasifatul syarifah; Wika Soviana Devi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
Literary work is of course influenced by the background and thoughts of the writer. This is commonly referred to as the extrinsic element. One of the literary works that has a strong extrinsic element is a drama script entitled Roh by Wisran Hadi. This work raises a tradition that contains animism and dynamism which is reflected in the tradition of summoning ancestral spirits. This drama turns out to have a correlation with the existing traditions in West Sumatra, the area from which Wisran Hadi originated, namely the Togak Balian tradition. This existing correlation becomes a tangible form of embodiment of extrinsic value in drama. Keywords: drama, animism, dynamism, Togak Balian, West Sumatra, extrinsic